O ensino de arquitetura como agente transformador da prática profissional - Joao de Paula Lima Neto (2007)
This work aims to analyze the architectural teaching of today and how it can be the transformer piece within the professional practice, passing over the teaching approaches initiated by the Traditional, which considers the educational conception and practice that remained through time, in its different forms, and started to be a reference to all other that succeeded it: the Behavioral, the Humanist, the Cognitive, the Sociocultural and the ones which intend to offer a more compatible reference to the conditions of contemporary world. This study considers that the architectural teaching should not focus on only one approach, but merge the positive aspects that each one has to contribute to knowledge, standing out that each individual has his own Time, and ought to be respected, so one could develop and produce more efficiently. An analysis of the methodof assessment, its application and legitimacy in Brazilian educational system is made in this piece. Furthermore, it outlines the higher education architecture courses situation within the central countries and current Brazilian circumstance. Through qualitative research, this work presents issues related to teaching and learning of architecture, endeavoring to get impressions of lived experiences, globally, from active professionals, as well as the ones that are being experienced by todays students; it also proposes alternatives to break the barriers which surround them. Naturally, it is not meant to close down sucha vast subject, but to try to put architectural teaching closer to the profession practice itself and consequently join praxis to theoretical knowledge, collaborating thus on the qualification of the architect and the educator.